Faktor-Faktor Yang Mempengaruhi Capaian Target Penanganan Komplikasi Obstetri Di UPTD Puskesmas Sekar Jaya Kabupaten Ogan Komering Ulu - Dina Fatmawati (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2021)
One of the obstetric complications is influenced by the mother's reproductive status or commonly known as 4 T (too young, too old, too close, too often). Every pregnant woman faces the risk of physical, mental burden and danger of complications of pregnancy, childbirth and childbirth with the risk of death, disability, dissatisfaction and discomfort. This study aims to determine the factors that affect the achievement of the target for handling obstetric complications. The method used is an analytical survey with a cross-sectional approach, where all variables are collected at the same time, the total population is all. The target achievement of handling obstetric complications in the work area of the Sekar Jaya Community Health Center UPTD in June-August 2020, amounting to 76 respondents and a sample of 76 people using the non-random sampling method with purposive sampling technique. The results of the study included length of work, knowledge of midwives and attitudes of midwives towards the achievement of targets for handling obstetric complications with p value = 0.03, 0.02. And 0,000. The conclusion of this study found that there was a significant relationship between length of work, knowledge of midwives and attitudes of midwives towards the achievement of targets for handling obstetric complications. It is hoped that it can provide information for parties in an effort to improve the ability of birth attendants / midwives to cope with handling the obstetric complications, especially in pregnancy, childbirth, childbirth and LBW